2023
DOI: 10.3390/plants12142669
|View full text |Cite
|
Sign up to set email alerts
|

Economic Uses of Salt-Tolerant Plants

Abstract: Climate change is likely to affect the ability of world agricultural systems to provide food, fibre, and fuel for the growing world population, especially since the area of salinised land will increase. However, as few species of plants (less than 1% of all plant species) can tolerate saline soils, we believe it is important to evaluate their potential as crops for salinised soils. We have analysed the economic and potential economic uses of plants that are listed in the database eHALOPH, including the most to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 109 publications
0
6
0
1
Order By: Relevance
“…Although the shoot biomass was sharply decreased by 200 and 400 mM NaCl, the shoots still grew with the formation of new shoots and leaves (Figure S2). This result indicated that P. nodiflora had a tolerance to high salinity and could be considered as a salt-tolerant plant that could become a useful plant material for studies on salt tolerance mechanisms [4].…”
Section: Effects Of Salinity On Biomass Of Shootsmentioning
confidence: 86%
See 2 more Smart Citations
“…Although the shoot biomass was sharply decreased by 200 and 400 mM NaCl, the shoots still grew with the formation of new shoots and leaves (Figure S2). This result indicated that P. nodiflora had a tolerance to high salinity and could be considered as a salt-tolerant plant that could become a useful plant material for studies on salt tolerance mechanisms [4].…”
Section: Effects Of Salinity On Biomass Of Shootsmentioning
confidence: 86%
“…Although the shoot biomass was sharply decreased by 200 and 400 mM NaCl, the shoots still grew with the formation of new shoots and leaves (Figure S2). This result indicated that P. nodiflora had a tolerance to high salinity and could be considered as a salt-tolerant plant that could become a useful plant material for studies on salt tolerance mechanisms [4]. In addition, it is proposed that salt-tolerant plants with potential uses for medicine, forage, essential oils, and biofuels can be developed for saline agriculture because the biomass reduction is not always proportional to their quality [22,23].…”
Section: Effects Of Salinity On Biomass Of Shootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garam merupakan komoditas pokok dengan beragam kegunaan di berbagai industri seperti industri kimia, industri makanan, industri farmasi, dan industri perminyakan. Ini digunakan sebagai bumbu untuk membumbui makanan dan meningkatkan rasanya (Garcia-Caparros et al, 2023). Garam juga digunakan dalam penyimpanan zat yang berguna atau berbahaya di bawah tanah, seperti minyak bumi atau limbah nuklir.…”
Section: Pendahuluanunclassified
“…In this sense, salt-tolerant wild plant species are interesting models for studies aimed at uncovering plant salt adaptation mechanisms [ 1 , 2 ]. On the other hand, there is interest in studying the properties of salt-tolerant plants in relation to their possible practical uses [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%